Corneal Densitometry as a Tool to Measure Epithelial Ingrowth After Laser In Situ Keratomileusis. Issue 4 (April 2017) - Adran, Daniel; Vaillancourt, Louis; Harissi-Dagher, Mona; Kruh, Jonathan N.; Syed, Zeba A.; Robinson, Steven; Melki, Samir
Abstract : Purpose: This study evaluates the correlation between corneal densitometry and epithelial ingrowth (EI) after laser in situ keratomileusis (LASIK). Methods: Corneal densitometry of 3 patients who developed EI after LASIK was measured with the Oculus Pentacam. Corneal densitometry readings of each patient were obtained preoperatively and postoperatively after ingrowth was discovered. Densitometry was recorded at the central nest of opacity and at the leading edges of EI. Results: For all patients, the most severe stages of EI observed on slit-lamp photographs correlated with the highest densitometry readings, with peak densitometry ranging from 73.3 to 95.1. These values were much higher than preoperative densitometry readings, which ranged from 21.8 to 27.2. In 2 cases, the Pentacam densitometry map revealed progression of EI toward the visual axis that was only faintly detectable or not detectable at all on the corresponding slit-lamp photographs. Conclusions: Corneal densitometry seems to be an objective measure of the severity and progression of EI after LASIK.